Análise da diversidade genética em erva baleeira (Varronia curassavica Jacq.) baseada no marcador ISSR - Brito, Fabiany de Andrade (2016)
Varronia curassavica Jacq. is a medicinal and aromatic plant from Brazil, with significant economic importance. Studies on genetic diversity in Active Germplasm Banks (AGB) are essential for conservation and breeding programs. The aim of this study was to analyze the genetic diversity of V. curassavica accessions of the Active Germplasm Bank of Medicinal and Aromatic Plants of the Federal University of Sergipe, using the Inter Simple Sequence Repeat (ISSR) molecular marker. DNA was extracted from 28 individuals by the CTAB 2% method. Twenty-four primers were tested, and 14 of them were polymorphic and informative, resulting in 149 bands amplified with 97,98% polymorphism. The Unweighted Pair Group Method with Arithmetic Mean divided the accessions into Cluster I and II. In the Jaccard similarity matrix, variation ranged between 0,24 and 0,78. The pairs of accessions VCUR- 001/VCUR-503, VCUR-001/VCUR-504 and VCUR-104/VCUR-501 showed higher diversity (0,24), and the pair of accessions VCUR-402/VCUR-403 showed medium diversity (0,78). Twenty-eight accessions were divided into three distinct clusters, according to the Structure analysis. According to the Principal Component Analysis (PCA), the first principal component accounted for 13,19% of the total variance, and the second principal component accounted 9,38% of the total variance. The genetic diversity of the Active Germplasm Bank of UFS is low to medium, and it requires expansion. VCUR-802 accession is the most suitable for selection in breeding program of this species, since it clearly represents all the diversity present in the germplasm Bank.